2022
DOI: 10.1038/s43247-022-00399-5
|View full text |Cite
|
Sign up to set email alerts
|

Boundary conditions representation can determine simulated aerosol effects on convective cloud fields

Abstract: Anthropogenic aerosols effect on clouds remains a persistent source of uncertainty in future climate predictions. The evolution of the environmental conditions controlling cloud properties is affected by the clouds themselves. Hence, aerosol-driven modifications of cloud properties can affect the evolution of the environmental thermodynamic conditions, which in turn could feed back to the cloud development. Here, by comparing many different cloud resolving simulations conducted with different models and under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…For example, it was recently shown that the representation of large‐scale effects on the CRM domain, that is, the lateral boundary conditions or “large‐scale forcing” (LSF), could artificially determine clouds' response to aerosol perturbation (Dagan, Stier, Spill, et al., 2022; Spill et al., 2021). Specifically, it was shown that the recent efforts to couple local cloud response with changes in the large‐scale vertical velocity (Abbott & Cronin, 2021) could result in an unrealistic increase in the environmental humidity and thus overestimate clouds' sensitivity to aerosols (Dagan, Stier, Spill, et al., 2022). The ongoing rise of global “storm‐resolving” (a few km resolution) models (Stevens et al., 2019) could lead to a significant advance in understanding the interactions between large‐scale circulation and local, smaller‐scale processes.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, it was recently shown that the representation of large‐scale effects on the CRM domain, that is, the lateral boundary conditions or “large‐scale forcing” (LSF), could artificially determine clouds' response to aerosol perturbation (Dagan, Stier, Spill, et al., 2022; Spill et al., 2021). Specifically, it was shown that the recent efforts to couple local cloud response with changes in the large‐scale vertical velocity (Abbott & Cronin, 2021) could result in an unrealistic increase in the environmental humidity and thus overestimate clouds' sensitivity to aerosols (Dagan, Stier, Spill, et al., 2022). The ongoing rise of global “storm‐resolving” (a few km resolution) models (Stevens et al., 2019) could lead to a significant advance in understanding the interactions between large‐scale circulation and local, smaller‐scale processes.…”
Section: Introductionmentioning
confidence: 99%
“…However, traditionally, these tools are unable to directly account for changes in the dynamics and thermodynamics of the large‐scale climate system, and hence lack an important component of clouds' response (Abbott & Cronin, 2021; Anber et al., 2019). For example, it was recently shown that the representation of large‐scale effects on the CRM domain, that is, the lateral boundary conditions or “large‐scale forcing” (LSF), could artificially determine clouds' response to aerosol perturbation (Dagan, Stier, Spill, et al., 2022; Spill et al., 2021). Specifically, it was shown that the recent efforts to couple local cloud response with changes in the large‐scale vertical velocity (Abbott & Cronin, 2021) could result in an unrealistic increase in the environmental humidity and thus overestimate clouds' sensitivity to aerosols (Dagan, Stier, Spill, et al., 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The added value of the EWIPS on top of the previous frameworks is the direct connection to top‐down constraints on the system, that is, the water and energy budgets. Recent work demonstrated the importance of considering water conservation in cloud resolving simulations, demonstrating that the representation of the water vapor convergence into the domain can determine the cloud response to aerosol perturbations (Dagan et al., 2022 ). Thus, exploring the sensitivity of the water and energy divergence to anthropogenic perturbations and its connection to cloud properties changes is of great importance.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, in addition to affecting the formation and development of DCCs, meteorology (before convection initiates) also regulates the distribution of aerosols, possibly leading to a non‐causal correlation between aerosols and DCCs. On the other hand, model simulations highlight that meteorological adjustments by PAI could further increase their association in a positive feedback loop (Abbott & Cronin, 2021; Anber et al., 2019; Dagan et al., 2022; Dagan & Stier, 2020). When aerosol increases, the enhanced evaporation of more but smaller droplet aloft moistens and cools the upper part of the cloud‐bearing atmospheric layer (Dagan et al., 2017).…”
Section: Introductionmentioning
confidence: 99%